DEVELOPMENT OF JAVANESE SCRIPT APPLICATION TO INCREASE LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS - Shofiyatul Muna; Achmad Buchori; Theodora Indriati Wardani (Universitas PGRI Semarang, 2023)
This research, which aims to increase the learning motivation of elementary school students, was conducted at Loireng State Elementary School. Research and Development (R&D) method were used to develop this Javanese script application. The subjects in this study were grade 5 (five) students at SDN Loireng. The results of motivation before and after using the Javanese script application amounted to 65% and 98%, it was concluded that the learning motivation questionnaire obtained the results of 46% of students in the moderate category. In normality testing, the results of the Asymp.Sig. (2-tailed) significance value of 0.000 < 0.05, so the data is not normally distributed. In the Wilcoxon Signed Rank Test test, it is known that Asymp.Sig. (2-tailed) is 0.000 because the value of 0.000 < 0.05. So it can be concluded that there is an influence on increasing the learning motivation of grade 5 (five) students of Loireng State Elementary School.